2016
DOI: 10.1042/cs20150699
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal vaccination with γ-irradiated Streptococcus pneumoniae whole-cell vaccine provides serotype-independent protection mediated by B-cells and innate IL-17 responses

Abstract: Generating a pneumococcal vaccine that is serotype independent and cost effective remains a global challenge. γ-Irradiation has been used widely to sterilize biological products. It can also be utilized as an inactivation technique to generate whole-cell bacterial and viral vaccines with minimal impact on pathogen structure and antigenic determinants. In the present study, we utilized γ-irradiation to inactivate an un-encapsulated Streptococcus pneumoniae strain Rx1 with an unmarked deletion of the autolysin g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 62 publications
5
44
0
Order By: Relevance
“…We did not study a role of cellular immune responses in preventing Spn infection. Wilson, et al have shown that both humoral and cellular immune responses are required to protect against Spn infection [30], Antibody-independent immunity such as CD4-mediated and IL-17-mediated T-cell response and TLR-mediated innate responses may play critical roles in protection against Spn infection [28, 2, 12, 30, 11, 8, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…We did not study a role of cellular immune responses in preventing Spn infection. Wilson, et al have shown that both humoral and cellular immune responses are required to protect against Spn infection [30], Antibody-independent immunity such as CD4-mediated and IL-17-mediated T-cell response and TLR-mediated innate responses may play critical roles in protection against Spn infection [28, 2, 12, 30, 11, 8, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…For this assay, splenocytes from 3 mice from LTB, Sp GlpO, Sp GlpO adjunct or MalX-immunized group were harvested and concentrations of IFN-γ, interleukin (IL)-6, IL-10 and IL-17A were measured in supernatants of antigen-stimulated splenocytes at 72 h by sandwich ELISA, using mouse ELISA Ready-SET-Go kits (eBioscience; Cat Nos 88-7314-88, 88-7064-88, 88-7104-88, 88-7371-88, respectively), essentially as described recently (Babb et al, 2016). Concanavalin A was used as a control, and concentrations of cytokines in supernatants were determined relative to the standard curve generated using cytokine standards provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…The Th17 response deserves a special note because it could provide a serotype-independent defence mechanism involving B cells and innate interleukin (IL)-17 [61]. Furthermore, IL-17 producing CD4 T cells specific for one serotype were effectively de-colonizing another serotype not expressing the specific antigen [62,63].…”
Section: Protein Conjugate Vaccinesmentioning
confidence: 99%